139. Development of cefiderocol resistance in an Enterobacter hormaechei strain following prolonged antibiotic exposure. (15th December 2022) - Medernach, Rachel; Moore, William J; Nozick, Sophia; Alamri, Maha M; Kling, Kendall; Ison, Michael G; Chao, Qi; Bachta, Kelly E R; Rhodes, Nathaniel J; Ozer, Egon A; Hauser, Alan R
Abstract: Background: Cefiderocol (FDC) is a novel antimicrobial agent used for multi-drug resistant Gram-negative pathogens. To date, reports of mutations in β-lactamase and siderophore complex genes have been described and may contribute to FDC resistance. This case describes a New Dehli metallo-β-lactamase (NDM)-producing strain of Enterobacter hormaechei that developed FDC resistance following antibiotic exposure. Methods: Serial respiratory and blood cultures were collected from a lung transplant recipient throughout 72 days of hospitalization. Confirmatory susceptibility and combination minimal inhibitory concentration (MIC) testing were performed using broth dilution and E-test assays. Short-read sequencing libraries were prepared using a seqWell plexWell 96 kit, and whole-genome sequencing was performed using the Illumina NovaSeq platform. Reads from the sample genomes were aligned to the chromosome and three plasmid sequences of reference genome ENCL48880. Results: Four serial respiratory E. hormaechei isolates and one blood isolate were evaluated. Although initial isolates were susceptible to FDC (MICs 1-2 µg/mL), two respiratory isolates cultured after 41 days of FDC therapy had MICs of 128 µg/mL. The blood isolate remained FDC susceptible despite respiratory resistance. The combination of ceftazidime/avibactam and aztreonam was determined to be active via synergy MIC testing in all isolates, and aztreonam therapeutic drug monitoring confirmed an adequate dosing strategy. Whole-genome sequencing revealed no nonsynonymous single nucleotide variants (SNVs) within the chromosomes but identified a deletion of a large urease island in the resistant isolates. In four of the five isolates, a plasmid (p48880_mcr) was identified and analyzed for possible contributions to FDC resistance. Enterobacter Isolate Assemblies This figure demonstrates genomic assemblies from the five Enterobacter clinical isolates, noting an absence of sequence from ECResp2. Conclusion: This case demonstrates development of FDC resistance in E. hormaechei isolates during a 41 day course of FDC therapy. Possible causes of resistance include a large chromosomal deletion and plasmid alleles, demonstrating a potential novel mechanism for FDC resistance. Partnering molecular testing and enhanced antimicrobial stewardship should be encouraged to optimize selection of regimens and durations to prevent resistance to FDC. Disclosures: Michael G. Ison, MD MS, GlaxoSmithKlein: Grant/Research Support|Pulmocide: Grant/Research Support|Viracor Eurfins: Advisor/Consultant Nathaniel J. Rhodes, PharmD, MSc, American Academy of Colleges of Pharmacy: Grant/Research Support|Paratek: Grant/Research Support|Third Pole Therapeutics: Advisor/Consultant.